Hypertension guideline recommendations in general practice: awareness, agreement, adoption, and adherence. - Heneghan, C; Perera, R; Mant, D; Glasziou, P (2007)
BACKGROUND: GPs vary greatly in their clinical management of hypertension, for reasons that are poorly understood. AIM: To explore GPs' awareness of current hypertension guidelines and their self-reported implementation of them in clinical practice. DESIGN OF STUDY: Questionnaire survey via the internet. SETTING: Primary care. METHOD: Survey of GPs (n = 401), based on the 'awareness-to-adherence' model of behavioural change. RESULTS: While awareness of recommendations was high, agreement and adoption were often less so. Almost all practitioners (99%) were aware of the guidance on statin therapy but fewer than half (43%; 95% confidence interval [CI] 38-48%) adhered to the recommendation in practice. Three-quarters (77%) were aware that blood pressure should initially be measured in both arms, but only 30% agreed with the recommendation (95% CI = 26 to 34%), and 13% (95% CI = 10 to 16%) adhered to it. Although the adoption of a recommendation was usually consequent on agreement with it, 19% of GPs (95% CI = 15 to 23%) reported adherence to financially incentivised guidance on statin therapy without either being aware of it or in agreement with it. No significant association was found among age, sex, year of graduation, or post held and level of awareness, agreement, or adoption. CONCLUSION: The specific barrier and action needed to promote application of hypertension guidelines varies with each clinical action. Lack of awareness is seldom the problem. Most GPs are unlikely to implement elements of guidance they disagree with even if given financial incentives. High adherence requires a reflective workforce that can respond to the scientific evidence underpinning the guidance.